Obstetric and Perinatal Outcomes in Preterm Prelabor Rupture of Membranes: A Two-Year Retrospective Analysis (Bangladesh Journal of Medical Science, 2026)
Objective To evaluate the structure of obstetric complications and the pattern of perinatal morbidity in preterm prelabor rupture of membranes (PPROM) based on a retrospective analysis of clinical data from three obstetric institutions in Aktobe (Aktobe region, Republic of Kazakhstan) over a two-year period. Materials and Methods A retrospective study including 428 women with singleton pregnancies complicated by PPROM who delivered in three perinatal institutions was conducted. Clinical and obstetric characteristics, duration of the latency period, mode of delivery, obstetric complications, and perinatal outcomes were analyzed. Statistical analysis included the χ² test, Spearman correlation analysis, and ROC analysis to assess the prognostic value of the duration of the latency period. Results An increase in the duration of the latency period was significantly associated with a higher incidence of chorioamnionitis and an increased rate of cesarean delivery (p < 0.001). A prolonged latency period was accompanied by a higher incidence of intrauterine infection and lower Apgar scores (r = −0.357; p = 0.001), whereas respiratory distress syndrome was more frequently observed when the latency period exceeded 168 hours. ROC analysis demonstrated a moderate but statistically significant predictive value of the duration of the latency period for intrauterine infection (AUC = 0.62; p < 0.001). Conclusion The duration of the latency period in PPROM is an important factor influencing the development of obstetric and perinatal complications. The findings support the need for an individualized approach to the management of pregnancies complicated by PPROM, taking into account the risk of infectious and neonatal complications.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 905-911